A Theorem of Nehari Type on Weighted Bergman Spaces of the Unit Ball - Yufeng Lu; Jun Yang (Abstract and Applied Analysis)
This paper shows that if S is a bounded linear operator acting on the weighted Bergman spaces Aα2 on the unit ball in ℂn such that STzi=Tz¯iS (i=1,…,n), where Tzi=zif and Tz¯i=P(z¯if); and where P is the weighted Bergman projection, then S must be a Hankel operator.